Digital Leadership and Employee Service Innovative A Perspective of Cognitive-Affective Processing System - Ayesha Sadaf; Ghazanfar Ali (`, 2026)
Employee’s service innovative behavior is essential for any organizations to involve innovative initiatives and achieve competitive advantages during digital transformation. Although numerous researches have examined the nexus of leadership with innovative behavior, the influence of digital leadership and the factors that cultivate innovative behavior remain ambiguous. The study employed the cognitive and affective processing system model to examine the dual mediating roles of creative self-efficacy and sense of belonging in the nexus of digital leadership with service innovative behavior. We measured the theoretical model hospitality sector of Pakistan. The design of the study was cross-sectional and quantitative with 5-point Likert Scale. The findings show that dual mediating paths are significant. The study has significant implications for comprehending the effect of digital leadership on significant workers’ outcomes. The limitations with direction for future research are discussed. Keywords: Sense of Belonging, Creative Self-Efficacy, Digital Leadership, Service Innovative Behavior